Blended Teaching Reform in Pathogenic Biology Experiment Course based on SPOC, Rain Classroom, and Virtual Simulation Platforms - Liu, Kai; Yuan, Fahu (International Journal of Social Sciences and Public Administration, 2025)
This study explores a novel blended teaching model that integrates Small Private Online Course (SPOC), Rain Classroom, and a Virtual Simulation Experiment Platform for the Pathogenic Biology Experiment course in medical education. The purpose of this instructional reform is to enhance students' theoretical knowledge, practical competencies, and learning engagement by bridging digital resources with in-person instruction. A quasi-experimental design was implemented, comparing an experimental cohort (n=55) adopting the blended model and a control cohort (n=53) following traditional methods. Data were collected on academic performance, skill assessments, and satisfaction levels. The results demonstrated statistically significant improvements (P